Analysis of Patient Satisfaction, Work Motivation, and Employee Performance on Minimum Service Standards (SPM) at Nice Dental Care Clinic - Setiasih; Ida Adhani; Aris Priyanto; Tukidi; Oktovina Deci R (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study attempts to ascertain the partial and joint analysis of employee performance, job motivation, and patient satisfaction with respect to basic service standards at the Nice Dental Care Clinic. Questionnaires are distributed as part of the quantitative approaches used in this study to collect data. 50 patients and staff members of the Nice Dental Care Clinic made up the study's sample, This was calculated with a 5% error rate using the Slovin algorithm (e). The analysis of data methods that are used coefficient of determination , T and F test. The factors of career growth, work environment, and mutation account for 2.9% of the work morale variable, whereas additional variables not included in the study do so. The t test results show that employee performance, work motivation and patient satisfaction partially influence the minimum service requirements. Employee performance, motivation if work, and patient happiness regarding minimum service requirements all have a large influence at the same time.